2012
DOI: 10.1002/ctpp.201200030
|View full text |Cite
|
Sign up to set email alerts
|

Wake Formation and Wake Field Effects in Complex Plasmas

Abstract: The formation of wake fields downstream of an objects in flowing plasmas has strong implications on structure, stability and dynamics of complex plasmas. This paper aims at putting recent experimental investigations and different theoretical approaches on charging of dust grains, stability of dust grain arrangements and the dynamical properties of complex plasmas into perspective. Further, the combination of wake fields and grain confinement is discussed, which is the generic situation in complex plasmas. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Vertically aligned particles, however, are levitated by an electric field that is stronger for the lower microparticle so that the two have different charges as was reported in Refs. [34,35,38,[68][69][70]. In the experiment by Carstensen et al [38], it was estimated that for their experimental conditions, the lower microparticle particle had a charge only 78% as large, i.e., Q β /Q α = 0.78.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…Vertically aligned particles, however, are levitated by an electric field that is stronger for the lower microparticle so that the two have different charges as was reported in Refs. [34,35,38,[68][69][70]. In the experiment by Carstensen et al [38], it was estimated that for their experimental conditions, the lower microparticle particle had a charge only 78% as large, i.e., Q β /Q α = 0.78.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…The neutral gas does not enter the DF directly but can modify the ion response considerably due to ion-neutral collisions ‡ For a more extensive list of earlier work see [11,12].…”
Section: Dielectric Function Approachmentioning
confidence: 99%
“…In the linear response (LR) formalism, e.g. 16,18,19 , the wake potential is linearly proportional to the grain charge, Q d . Winske et al 17 , however, found a nonlinear relationship between charge and wake potential utilizing one-and two-dimensional PIC-simulations.…”
Section: Introductionmentioning
confidence: 99%